Perempuan dan Perbankan: Sebuah Tinjauan Tentang Peran Inklusi Keuangan terhadap Pengusaha UMKM Perempuan di Indonesia - Steelyana, Evi (Bina Nusantara University, 2013)
Financial inclusion is a means to promote financial sector especially for easy banking services and financial access for people. Increasing living standard is one of the expected results when financial inclusion runs well. Financial inclusion program in Indonesia is expected to give significant impact to unprevillege people, such as: people with low income, fringe, minority, or having no legal identity and women and the young. This paper focuses on how financial inclusion can give a significant impact especially to woman in SME in Indonesia and how financial inclusion program can increase and strengthen Indonesian economy as a whole. Research used quantitative-descriptive method; comparative analysis was done based on secondary data from various sources. This research concludes that financial inclusion shall be conducted in Indonesia as a whole and may affect the SMEs significantly, especially women.